Optimalisasi Peran Orang Tua Dalam Pembelajaran Daring Pada Masa Pandemi Covid-19 di Kelurahan Sumber Harta - Peni Nur Syamsiah; Asih Rahmawati; Atika Atika; Indah Novita Wati; Yuliana Yuliana; Muhammad Faizul Amirudin (Edification Journal : Pendidikan Agama Islam, 2021)
Covid-19 has a very bad impact on human life. Many activities that are hampered are also limited because of this virus. The economic, social, political sectors including education are very affected. As a result, the world of education must carry out the learning process at home online. The most basic difference is that students cannot be directly with the teacher. So that the focus of students is very limited, considering many things that can interfere with student concentration when learning from home. Starting from this, it is what encourages parents to guide their children to learn with courage. is a challenge for parents. The situation is that parents must be technology literate in order to be able to guide children in school and provide full support for children to be able to learn well during the Covid-19 pandemic. This modern education pattern must still be implemented until conditions are back to conducive.